Effects of a self-care educational program via telerehabilitation on quality of life and caregiver burden in amyotrophic lateral sclerosis: a single-blinded randomized clinical trial protocol - Gomes de Souza e Silva, Emília Márcia; Tomaz da Silva, Stephano; Januário de Holanda, Ledycnarf; Tezoni Borges, Daniel; Mendonça Fernandes, Ana Paula; Evangelista Rodrigues da Silva, Kelly; Souza Ribeiro, Tatiana; Protásio de Melo, Luciana; de Medeiros Valentim, Ricardo Alexsandro; Alves Pinto Nagem, Danilo; Rodrigues Lindquist, Ana Raquel (Frontiers in Psychology, 2023)
The implementation of a telerehabilitation protocol for self-care in the routine of caregivers of individuals with amyotrophic lateral sclerosis (ALS) has been associated with reduced levels of stress and improved quality of life. Also, it may reduce the difficulty of traveling to perform physical or other self-care activities. Thus, this study designed a clinical trial protocol to investigate the effects of a self-care education program via telerehabilitation on the burden and quality of life of caregivers of individuals with ALS.Methods: This single-blinded randomized clinical trial will recruit 26 caregivers and randomly allocate them to the experimental (EG = 13) or control group (CG = 13). The EG will receive an informative booklet and participate in a six-week synchronous telerehabilitation program with a neuropsychologist, nutritionist, and physiotherapist to discuss physical and mental health. The CG will receive an informative booklet on self-care and physical activity and weekly phone calls for six weeks to solve questions about the booklet. Outcomes will include the caregiver burden (Zarit scale), quality of life (World Health Organization Quality of Life BREF), pain (McGill Pain Questionnaire), stress (Perceived Stress Scale), and depression (Beck Depression Inventory), which will be evaluated at baseline, after the six-week program, and 30 days after the program.Additionally, we will assess daily the nocturnal awakenings, sleep patterns, level of physical activity, and heart rate variability.